Who Displays Ethical Leadership, and Why Does It Matter? An Examination of Antecedents and Consequences of Ethical Leadership - Mayer, David M.; Aquino, Karl; Greenbaum, Rebecca L.; Kuenzi, Maribeth (Academy of Management Journal, 2012)
Drawing on social learning and moral identity theories, this research examines antecedents and consequences of ethical leadership. Additionally, this research empirically examines the distinctiveness of the ethical leadership construct when compared to related leadership constructs such as idealized influence, interpersonal justice, and informational justice. Consistently with the theoretically derived hypotheses, results from two studies of work units (n's = 115 and 195 units) provide general support for our theoretical model. Study 1 shows positive relationships between ethical leadership and leader “moral identity symbolization” and “moral identity internalization” (approaching significance) and a negative relationship between ethical leadership and unit unethical behavior and relationship conflict. In Study 2, both leader moral identity symbolization and internalization were positively related to ethical leadership and, with idealized influence, interpersonal justice, and informational justice controlled for, ethical leadership was negatively related to unit outcomes. In both studies, ethical leadership partially mediated the effects of leader moral identity.